Cognitive biases among early adolescents with elevated symptoms of anxiety, depression, and co‐occurring symptoms of anxiety‐depression. Issue 5 (23rd November 2016) - Weeks, Murray; Coplan, Robert J.; Ooi, Laura L.
Abstract: Anxiety and depression are often highly correlated in adolescence, and cognitive biases are commonly associated with both types of symptoms. The purpose of this study was to examine cognitive biases in early adolescents showing: (a) elevated symptoms of anxiety; (b) elevated symptoms of depression; (c) elevated co‐occurring symptoms of anxiety and depression; and (d) neither elevated symptoms of anxiety nor depression (comparison group). In particular, we were interested in the extent to which certain cognitive biases showed symptom specificity. Participants were N =  686 10‐ to 14‐year‐olds, who provided self‐reports of anxiety, depression, and measures of cognitive biases. Four groups were created based on quartile cutoffs: anxious, depressed, anxious‐depressed, and comparison . Among the results from multivariate analysis of variance, the anxious group thought negative events were more costly as compared to the depressed group. In contrast, the depressed group was higher in terms of negative causal attributions, overgeneralizing, selective abstraction, and negative views of the self, world, and future. The anxious‐depressed group showed an overall more negative pattern of cognitive biases than all other groups. Symptoms of anxiety and depression are distinguishable in terms of certain cognitive biases, and the co‐occurrence of symptoms is indicative of a particularly negative pattern of thinking. These findings have implications for intervention programs that could target specific cognitive biases. Highlights: Are distinct patterns of cognitive biases evident among early adolescents with symptoms of anxiety, symptoms of depression, and co‐occurring symptoms of anxiety and depression? We collected self reports of cognitive biases. We also collected self reports of anxiety, depression, and cognitive biases, and created the following groups: 1) anxious; 2) depressed; 3) anxious‐depressed; 4) comparison. Symptoms of anxiety and depression are distinguishable in terms of certain cognitive biases, and symptom co‐occurrence may indicate a particularly maladaptive pattern of thinking.